1,6-Conjugate addition initiated formal [4+2] annulation of p-quinone methides with sulfonyl allenols: a unique access to spiro[5.5]undeca-1,4-dien-3-one scaffolds - Ghotekar, Ganesh S.; Shirsath, Sachin R.; Shaikh, Aslam C.; Muthukrishnan, M. (Chemical Communications, 2020)
An expedient one-pot synthesis of carbocyclic spiro[5.5]undeca-1,4-dien-3-ones via 1,6-conjugate addition initiated formal [4+2] annulation sequences by employing p-quinone methides and sulfonyl allenols is presented. Furthermore, this synthetic protocol tolerates a wide variety of p-quinone methides and sulfonyl allenols and affords the corresponding structurally unique spiro[5.5]undeca-1,4-dien-3-ones in good yield under mild reaction conditions.